AWESOME FACTS (igloobooks, 2013)
Discover the 1000 most revolting facts ever! What flower smells of rotten flesh? Which creature can turn water into slime? Why do some people eat their own bogies? Which cave is completely covered in bat poo? Hold onto your stomach and get ready to discover the yuckiest things, people, places and animals in the universe!